Analisis Kesulitan Mahasiswa Pendidikan Fisika FKIP-UNDANA Dalam Memahami Materi Volume Benda Putar - Rimo, Imelda Hendriani Eku (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2018)
The purpose of this study was to describe the difficulties of students of Physical Education, Faculty of Teacher Treaning and Education, The University of Nusa Cendana, in understanding the material volume of rotary an area. This type of research is descriptive qualitative. The subject of the study was taken from students of the Physics Education second semester, Faculty of Teacher Treaning and Education, The University of Nusa Cendana, as many as 42 people. Data was obtained through tests and documentation of student work results. The results revealed that there were 3 types of difficulties experienced by physics education students of the University of Nusa Cendana, namely (1) difficulty understanding the concept, such as the difficulty in applying the method used correctly, difficult to determine the upper limit and lower limit of certain integrals that were appropriate to the problem and difficult to determine the right function to be countered. (2) difficulty in calculating accuracy, such as not being careful in calculating multiplying positive numbers with negative numbers and squaring a function. (3) difficulty in image representation. Keywords: Volume of rotating an area, difficulty